Kualitas Buku Teks Mini Sejarah Indonesia Karya Mahasiswa Jurusan Sejarah Fakultas Ilmu Sosial Universitas Negeri Padang - Nurlaili Nurlaili; Aisiah Aisiah (PAMA Aksara, 2021)
This study aims to determine the quality of the mini-textbook of Indonesian History by students of the Department of History in grades X, XI and XII. This research is evaluative research with a quantitative approach. The source of the research data was from the results of the assessment of the Indonesian History mini-textbook which was assessed by six raters, namely three history teachers and three students of the Department of History. The mini-textbook of Indonesian history is worth three books, one each consisting of grades X, XI, and XII. The research instrument used an assessment sheet for the Indonesian History mini-textbook. Data analysis used descriptive analysis with percentage technique. The results of the study on the quality of the mini-textbooks assessed by the History Teacher class X were categorized as very good with the percentage results of 84% and 78% being assessed by the students of the History Department, the XI class assessed by the History Teacher was categorized as very good with the percentage results of 79% and 81% being assessed by History Department Students, class XII assessed by History Teachers was categorized as very good with a percentage of 86% and 79% assessed by History students.